Qual o Planejamento Regional na Sociedade de Risco? Reflexões para uma Renovação da Agenda de Pesquisa no Rio Grande do Sul - Markus Erwin Brose (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2019)
The perception of risks due to climate change encourages a re-discussion of research priorities on regional planning. Climate change is not just an ‘environmental issue’, it alters power relations in markets, by changing prices, and in politics, through new costs. This article aims at an empirical reflection, contributing to integrate resilience as a transversal dimension in regional planning. He uses aspects of the Society of Risk theory, proposed by sociologist Ulrich Beck, discussing connections with the work of Anthony Giddens, especially his proposal of the New Green Deal. We argue that, contrary to Giddens’ optimism as to the capacity of the state, it is possible to recognize in Rio Grande do Sul evidence of the exhaustion of the classic redistributive conflicts of capitalism, and that increasing uncertainties stimulate the renewal of research priorities in regional planning.